O wzorach i sposobach mówienia o ojczyźnie w wybranych tekstach Wielkiej Emigracji = On patterns and ways of talking about the homeland in some statements from the partitions era - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of discussion is the way of verbalizing and implementing the patterns of talking about "homeland" formed by Polish tradition and culture in the texts of the democratic camp of the Great Emigration in the partitions era. The tested material has shown that "homeland" was recognized as the highest value belonging to the realm of the sacred, which was reflected in its depiction in terms of apotheosis and glorification.
Keywords: ojczyzna; sakralizacja; personifikacja; wzór mówienia; apoteoza; sacrum narodowe; homeland; sanctification; personification; pattern of speaking; apotheosis; the national sacred